2010
DOI: 10.1007/s12572-011-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Processing and biological evaluation of porous HA/poly(methyl methacrylate) hybrid composite

Abstract: The present study reports the preparation and characterization of dense and porous hydroxyapatite scaffolds for bone regeneration. Porous hydroxyapatite scaffolds were prepared via polymer blend method using poly(methyl methacrylate) as porogenous template to obtain micro-and meso level porosity. The pore size in the sintered ceramics was in the range of 1-50 lm. Hydroxyapatite porous scaffolds were characterized, using X-ray diffraction, Fourier Transformed Infrared Spectroscopy and Scanning Electron Microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a different processing approach, microporous HA scaffolds are prepared using PMMA as a sacrificial additive. 9 In the last decade, limited efforts have been invested to fabricate and characterize gelatin-HA scaffolds. [10][11][12][13] Such studies often reported either the fabrication aspects of these porous scaffolds, or the response of osteoblast/human mesenchymal stem cells on the scaffold under static or dynamic culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a different processing approach, microporous HA scaffolds are prepared using PMMA as a sacrificial additive. 9 In the last decade, limited efforts have been invested to fabricate and characterize gelatin-HA scaffolds. [10][11][12][13] Such studies often reported either the fabrication aspects of these porous scaffolds, or the response of osteoblast/human mesenchymal stem cells on the scaffold under static or dynamic culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For developing porous scaffolds, it is important that they meet certain requirements of bone tissue engineering and integrate well with the bone healing process. Some of the important aspects that need to be considered while developing these scaffolds are: appropriate micro-and macroscopic structural morphology including pore size, pore interconnectivity, biocompatibility, osteoconductivity, mechanical strength and biodegradability [40]. The idea is that if an implanted porous ceramic is progressively replaced by natural bone, its biomechanical properties should more and more resemble with natural bone.…”
Section: Properties Of Porous Calcium Phos-phatementioning
confidence: 99%